Echoes of silence: Evaluating the effects of audience restrictions on elite golf performance - Lundkvist, E.; Larsson, R.; Kalén, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction The unique circumstances of the COVID-19 pandemic offered an opportunity to study the effect of audience presence on athletic performance. This research focused on professional golf, an individual sport where performance can be quantitatively measured, providing a clear view of the impact of spectators. Drawing on theories of social facilitation [2, 3] and psychological pressure[4], this study aimed to explore how the presence, absence, and limited presence of spectators influenced PGA TOUR golfers performances over the 2018-2022 seasons. This exploration is rooted in the broader context of how environmental factors affect athletic performance, contributing to the ongoing discussion in sports psychology and performance analysis. Methods The performance of 832 professional golfers across five seasons (103 00 golf rounds) of the PGA TOUR was analysed before, during and after audience restrictions. Performance metrics were examined using two-level linear mixed models [1]. Results The findings revealed a complex relationship between audience presence and golfer performance. Overall, players performed best in the absence of spectators. Conversely, the presence of an audience following the pandemic showed better performance levels than with audience before the pandemic, indicating a possible effect of the decision making learned without an audience. Notably, experience and skill level of the players did not interact with these results. Discussion The study highlights the nuanced interplay between athlete performance and audience presence, suggesting that presence of spectators influence professional golfers performance. This research extends the understanding of social facilitation in sports, emphasizing the need for personalized approaches in athlete preparation and coaching. Future research directions include using underlying performance measurements to understand what parts of the game where the players performed differently, qualitative interviews to get the players experiences of playing with and without an audience and physiological measurements to further understand what might cause the differences.